The Effect Of Job Satisfaction And Work Environment On Increasing Work Productivity At Pt. Pondok Indah Padang Golf Company - Reza Farlevi; Sunarti Sunarti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of job satisfaction and work environment on employee productivity at PT. Pondok Indah Padang Golf. Using a sample of 65 employees selected through a saturated sampling method, data were collected using a Likert scale-based questionnaire. The analysis was conducted using multiple linear regression with SPSS v20. The results show that job satisfaction and work environment significantly influence productivity, with an R² value of 0.55. The t-test results are 4.23 for job satisfaction and 3.87 for the work environment, while the F-test results a value of 37.308 (p < 0.05). These findings indicate the need to enhance job satisfaction through salary adjustments, promotions, and interpersonal relationships, as well as optimizing the work environment by improving lighting, controlling temperature, and reducing noise to boost employee productivity.